Mess is more: Radical democracy and self-realisation in late-modern societies. (April 2019) - Ebert, Norbert
The following discussion highlights the sociological relevance of Maria Márkus's work for the Budapest School's concept of 'radical democracy'. A brief historical sketch exhibits how the concept has emerged. It is in particular the 'messy' social conditions for equal and free forms of self-realisation in civil society that underpin radical democracy which are central in Maria Márkus's critique of the neoliberal state, identity formation and a gendered achievement principle. Her approach, I argue, can be advanced as a prism for the critical analysis of contemporary issues. To do so, I contend that late-modern societies are increasingly defined by a paradox with a pluralisation of identity claims in civil society on the one hand, and tendencies to homogenise identities on the other by concurring economic and political forces. A democratisation of everyday life, and with it diverse and plural forms of self-realisation, appears to be under homogenising pressures from governments and markets alike. This will be briefly demonstrated using Maria Márkus's work, which also points toward possible departure points to advance a critical sociology of radical democracy.